PELECEHAN SEKSUAL TERHADAP TOKOH DALAM NOVEL SEPERTI DENDAM RINDU HARUS DIBAYAR TUNTAS KARYA EKA KURNIAWAN: KAJIAN HARGA DIRI ROSENBERG: Sexual harassment of characters in novels Seperti Dendam Rindu Harus Dibayar Tuntas (Revenge Must Be Paid in Full) by Eka Kurniawan: Rosenberg's self-esteem study - Adnan, A. Adelia Firddauzha; Nensilianti; Hajrah (Journal of Applied Linguistics and Literature, 2025)
This study aims to describe the forms of sexual harassment and the relationship between sexual harassment and the dimensions of self-esteem in the characters in Eka Kurniawan's novel Seperti Dendam, Rindu Harus Dibayar Tuntas which is used as the source of analysed data. This research uses descriptive qualitative method by describing the data obtained based on Fitzgerald and Schullman's views on sexual harassment and Rosenberg's Self Esteem theory. The data source of this research is the novel Seperti Dendam, Rindu Harus Dibayar Tuntas by Eka Kurniawan. The results showed that there are five levels of sexual harassment on the characters in Eka Kurniawan's novel Like Revenge Longing Must Be Paid Completely in accordance with Fitzgerald and Schullman's views, namely gender harassment, seduction behaviour, sexual bribery, sexual coercion, and sexual imposition. Then there are also three aspects of Rosenberg's self-esteem dimension that are related to sexual harassment of characters in Eka Kurniawan's novel Like Revenge, Rindu Must Be Paid Completely, namely physical self-esteem (physical appearance), social self-esteem (social skills), and performance self-esteem (academic ability). Based on the analysis, it is found that the perpetrator's self-esteem is the cause of sexual harassment and the impact of sexual harassment on characters who experience sexual harassment